Clinical study of exhaled nitric oxide in children with asthma and allergic rhinitis - LI Pengyun; DAI Yinfang; LU Yanhong; YU Xingmei; XU Lina; DI Wujianfeng; HAO Chuangli (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2023)
Objective·To determine the levels of nasally exhaled nitric oxide (FnNO) combined with fractional concentration of exhaled nitric oxide (FeNO) in children with asthma (AS) complicated with allergic rhinitis (AR), and analyze the levels of FnNO and FeNO in different clinical stages of AS with different severities of AR, so as to provide basis for guiding clinical diagnosis and treatment.Methods·Children diagnosed with AR with AS in the Department of Respiratory and Otolaryngology of Children's Hospital of Soochow University from April 2021 to November 2021 were included, and healthy children who visited the Department of Pediatrics for normal physical examination during the same period were enrolled as the control group. FeNO and FnNO were measured in all children to assess the severity of the children's diseases. The levels of FeNO and FnNO in children with AR and AS at different clinical stages of AS and their correlation with pulmonary function were compared and analyzed.Results·The proportion of persistent moderate-to-severe rhinitis was higher in the acute exacerbation stage of AS, and the proportion of intermittent mild rhinitis was higher in the clinical remission stage of AS. The FeNO level in the acute exacerbation stage were higher than that in the chronic persistent stage and clinical remission stage of AS (adjusted P=0.022, 0.000), and higher in the chronic persistent stage than that in the clinical remission stage of AS (adjusted P=0.002). The FnNO level in the acute exacerbation stage was higher than that in the clinical remission stage of AS (adjusted P=0.044). In the chronic persistent stage of AS, the FnNO levels in the persistent mild group and persistent moderate-to-severe control group were higher than those in the intermittent mild group (adjusted P=0.001, 0.000). In the clinical remission stage of AS, the FnNO levels in the persistent mild group and persistent moderate to severe control group were higher than those in the intermittent mild group (adjusted P=0.001, 0.007). In the intermittent mild group of AR, the FnNO levels in the acute exacerbation stage were higher than those in the chronic persistent stage and clinical remission stage of AS (adjusted P=0.010, 0.019). Part of pulmonary functions in the acute exacerbation stage of AS children were negatively correlated with the FeNO and FnNO levels (all P<0.05), while FEV1/pred in the chronic persistent stage was negatively correlated with FeNO level (P=0.010).Conclusion·FeNO and FnNO levels increased in the acute exacerbation stage of AS, and symptom scores of AR also increased. FeNO and FnNO levels were negatively correlated with pulmonary function in AS with AR children.